2011
DOI: 10.1007/s13197-011-0323-2
|View full text |Cite
|
Sign up to set email alerts
|

Retention of carotenoids in orange-fleshed sweet potato during processing

Abstract: The retention of carotenoids was studied in the storage roots of ten sweet potato clones possessing different intensities of dark orange-flesh colour in four different processing methods-oven drying, boiling, sun drying and frying. The results indicated that the extent of retention varied with the method of processing. The highest retention was observed in oven drying (total carotenoids 90%-91% and β-carotene 89%-96%) followed by boiling (total carotenoids 85%-90% and β-carotene 84%-90%) and frying (total caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 19 publications
3
52
3
1
Order By: Relevance
“…Studies related to this theme are divergent, since the carotenoid content can be reduced (GAYATHRI et al, 2004), do not change, or even increase (VIMALA et al, 2011) after cooking. Normally, heat processing method can reduce the carotenoid content as a result of the susceptibility of these compounds to degradation and isomerization under high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Studies related to this theme are divergent, since the carotenoid content can be reduced (GAYATHRI et al, 2004), do not change, or even increase (VIMALA et al, 2011) after cooking. Normally, heat processing method can reduce the carotenoid content as a result of the susceptibility of these compounds to degradation and isomerization under high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Globally, the processing methods that result in the highest levels of retention are: boiling/steaming (80-90%) [3,10], roasting, frying (70-80% [11] and sun/solar drying (60-80%) [3,4,8,9,11,12]. Sun-drying resulted in the lowest levels of retention when tested in Uganda, Mozambique, and Tanzania.…”
Section: Sweet Potatomentioning
confidence: 99%
“…Consumers enjoy the pleasant odor and flavor of baked sweet potatoes. Although chemical composition analysis of sweet potatoes has been previously documented (Ahmed et al 2010;Ahromrit and Nema 2010;Aina et al 2009;Picha 1985;Picha 1986;Vimala et al 2011), little information on the effect of baking has been reported (Lai et al 2011).…”
Section: Introductionmentioning
confidence: 99%